Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.3 - Polynomial Functions, Graphs, and Composition - 4.3 Exercises: 29

Answer

$x^{2}-x-6$

Work Step by Step

We are given that $f(x)=x^{2}-9$, $g(x)=2x$, and $h(x)=x-3$. We are asked to find the value of $(f-h)(x)$. We know that $(f-h)(x)=f(x)-h(x)$. Therefore, $(f-h)(x)=(x^{2}-9)-(x-3)=x^{2}-x-9+3=x^{2}-x-6$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.